THE ROLE OF ECONOMIC DEVELOPMENT IN SOUTH SUDAN POLICY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
A society develops economically a society is recognizedas developed when it members increase jointly their capacity for dealing with the environment(Habasonda, 2013). This capacity is dependent on the extent to which they understand the laws of nature (science), and on the extent to which they put that understanding into practice by devising tools (technology), and on the manner in which work is organized (United Nations, 2011).Modern democratic societies rely on the power of education and the media to get the word around about what problems we collectively face. Those societies whose citizens are encouraged to engage in the fullest and most enlightened exercise of choice will have the greatest potential for development(Habasonda, 2013).